Corrosion-resistant polypropylene edge band material and preparation method thereof

By adding corrosion resistance and composite flame retardant to the polypropylene edge sealing strip material, the problems of poor corrosion resistance, heat resistance and flame retardant properties of the polypropylene material are solved, and multiple performance improvements of the material are achieved.

CN119823494AActive Publication Date: 2025-04-15GUANGDONG ZHAOQING OUDA DECORATION MATERIAL CO LTD

Patent Information

Application Number
CN202510107007.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-15
Estimated Expiration
2045-01-23

AI Technical Summary

Technical Problem

The corrosion resistance, heat resistance and flame retardant properties of existing polypropylene materials are poor.

Method used

The formulation of 50-75 parts of polypropylene, 2-5 parts of antioxidant, 3-6 parts of corrosion resistance, 2-4 parts of composite flame retardant, 8-15 parts of calcium carbonate and 2-4 parts of dye was prepared by preparing corrosion resistance and composite flame retardant, which were prepared from 2,6-dichlorobenzonitrile, 1,2,4-triazole, sulfuric acid solution, sodium nitrite and parachloroaniline, as well as 3-glycidyl etheroxypropyltrimethoxysilane, diphenylsilicol, barium hydroxide and boric acid, respectively, and added to the polypropylene edge strip material.

Benefits of technology

The corrosion resistance, heat resistance, flame retardancy and mechanical properties of polypropylene edge sealing strip materials are significantly improved, meeting the requirements of high-end furniture for material performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a corrosion-resistant polypropylene edge band material and a preparation method thereof, and belongs to the technical field of preparation of edge band materials. The corrosion-resistant polypropylene edge sealing strip material is prepared from, by weight, 50-75 parts of polypropylene, 2-5 parts of an antioxidant, 3-6 parts of a corrosion-resistant agent, 2-4 parts of a composite flame retardant, 8-15 parts of calcium carbonate and 2-4 parts of dye, the corrosion-resistant agent is prepared from 2, 6-dichlorobenzonitrile, 1, 2, 4-triazole, a sulfuric acid solution, sodium nitrite and parachloroaniline, and the corrosion-resistant agent is prepared from 2, 6-dichlorobenzonitrile, 1, 2, 4-triazole, a sulfuric acid solution, sodium nitrite and parachloroaniline. The composite flame retardant is prepared from 3-glycidyl ether oxypropyl trimethoxy silane, diphenyl silanediol, barium hydroxide and boric acid. The edge band material prepared by the method has excellent corrosion resistance, flame retardance, heat resistance and mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of edge banding material preparation, and in particular relates to a corrosion-resistant polypropylene edge banding material and a preparation method thereof. Background Art

[0002] As a semi-crystalline thermoplastic, polypropylene has excellent physical and chemical properties and is widely used in many fields. Its molecular structure is compact, there is no polar group, it has excellent chemical stability, and it can resist the erosion of various acids and alkalis, including some organic solvents, showing excellent chemical corrosion resistance. This feature makes polypropylene an ideal choice for manufacturing corrosion-resistant edge banding materials. In addition, polypropylene is also an environmentally friendly material, non-toxic and odorless, recyclable and reusable, in line with modern environmental protection concepts, and can meet consumers' pursuit of healthy and environmentally friendly life.

[0003] In the field of furniture manufacturing, the performance of edge banding directly affects the durability and aesthetics of furniture. Although traditional PVC edge banding is light in weight, easy to process, and has certain oil resistance, heat resistance, and wear resistance, its quality is unstable, the color difference is obvious after trimming, and it is easy to age and break, which cannot meet the material performance requirements of high-end furniture. Although ABS edge banding is wear-resistant, corrosion-resistant, aging-resistant, fire-proof, moisture-proof, green and environmentally friendly, has good dimensional stability, and strong impact resistance, its production cost is high and its price is expensive, which limits its application. Polypropylene edge banding inherits the multiple advantages of polypropylene materials, and has many advantages such as light weight, wear resistance, environmental protection and odorlessness, and high softening point, making it the preferred material for furniture manufacturing.

[0004] Patent CN112574500B discloses a high-rigidity and high-heat-seal strength polypropylene material and a preparation method thereof, wherein the components are: 88.5-94.2% polypropylene resin; 5-10% reinforcing agent; 0.7-1.5% other auxiliary agents; the reinforcing agent is modified wollastonite; the preparation method is: weigh half of the polypropylene resin in the feed amount and put it into a high-speed mixer, then put other raw materials except the modified wollastonite into the mixer, and mix them fully to obtain a mixture; put the mixture into the main feed inlet of the extruder, add the modified wollastonite from the side feed inlet of the extruder, extrude and granulate to obtain wollastonite masterbatch, and the melt extrusion temperature is 185-200°C; the wollastonite masterbatch is evenly mixed with the remaining half of the feed amount of polypropylene resin to prepare a polypropylene material with high strength and high heat-seal strength, but the corrosion resistance, heat resistance and flame retardancy of the polypropylene material prepared by this method still have room for improvement. Summary of the invention

[0005] The object of the present invention is to provide a corrosion-resistant polypropylene edge banding material and a preparation method thereof, so as to solve the technical problem that the corrosion resistance, heat resistance and flame retardancy of polypropylene materials in the prior art are poor.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] The invention provides a corrosion-resistant polypropylene edge banding material, which is composed of the following components in parts by weight: 50-75 parts of polypropylene, 2-5 parts of antioxidant, 3-6 parts of corrosion retardant, 2-4 parts of composite flame retardant, 8-15 parts of calcium carbonate, and 2-4 parts of dye, wherein the corrosion retardant is prepared from 2,6-dichlorobenzonitrile, 1,2,4-triazole, sulfuric acid solution, sodium nitrite and p-chloroaniline, and the composite flame retardant is prepared from 3-glycidyloxypropyltrimethoxysilane, diphenylsilanediol, barium hydroxide and boric acid.

[0008] Preferably, the antioxidant consists of one or more of antioxidant 1010 , antioxidant 1076 , antioxidant 168 and antioxidant 626 .

[0009] Preferably, the method for preparing the corrosion resistant agent comprises the following steps:

[0010] Q1: Add 2,6-dichlorobenzonitrile, 1,2,4-triazole and anhydrous potassium carbonate to a container containing N,N-dimethylformamide, heat to react, and after the reaction is completed, filter under reduced pressure and repeat the operation to obtain intermediate 1;

[0011] Q2: Add intermediate 1 to a container, then add sulfuric acid solution, heat to react, add distilled water after the reaction is completed, adjust the pH, filter under reduced pressure, extract, dry and distill the filtrate under reduced pressure to obtain intermediate 2;

[0012] Q3: Add intermediate 2 to a container placed in an ice bath, add sulfuric acid solution, wait for the temperature of the reaction solution to drop, dropwise add distilled water containing sodium nitrite, continue the reaction after the dropwise addition is complete, then increase the temperature to react, extract, dry, and distill under reduced pressure after the reaction is complete to obtain intermediate 3;

[0013] Q4: Add intermediate 3 to a container with toluene and a reflux and gas collection device, slowly add thionyl chloride under heating conditions to react, treat under negative pressure, add toluene, add p-chloroaniline, heat to react, add triethylamine dropwise during the reaction, wash after the reaction, let stand to separate, wash the organic phase, dry, filter, evaporate to dryness under negative pressure to obtain a corrosion inhibitor.

[0014] In the above process, 2,6-dichlorobenzonitrile is condensed with 1,2,4-triazole in the presence of anhydrous potassium carbonate using N,N-dimethylformamide as a medium to obtain intermediate 1, and then intermediate 1 is hydrolyzed in a sulfuric acid solution to be converted into intermediate 2, and then intermediate 2 is converted into intermediate 3 by diazotization and hydrolysis, and intermediate 3 is prepared in the presence of thionyl chloride and p-chloroaniline to obtain a corrosion inhibitor, wherein the synthetic reaction formula of the corrosion inhibitor is as follows:

[0015] The results of mass spectrometry analysis of intermediate 1 were: m / z: 204.02 (100.0%), 206.02 (32.1%), 205.02(11.2%), 207.02 (3.1%); the results of mass spectrometry analysis of intermediate 2 were: m / z: 222.03 (100.0%), 224.03(32.1%), 223.03 (11.2%), 225.03 (3.2%); the results of mass spectrometry analysis of intermediate 3 were: m / z: 223.01(100.0%), 225.01 (32.0%), 224.02 (9.9%), 226.02 (3.2%), 224.01 (1.1%), 225.02 (1.0%); the results of mass spectrometry analysis of the corrosion-resistant agent are: m / z: 332.02 (100.0%), 334.02 (64.2%), 333.03 (16.4%), 335.02 (11.3%), 336.02 (10.5%), 337.02 (1.7%), 333.02 (1.5%), 334.03 (1.5%).

[0016] Preferably, in Q1, the dosage ratio of 2,6-dichlorobenzonitrile, 1,2,4-triazole, anhydrous potassium carbonate and N,N-dimethylformamide is (1-1.5) g: (0.6-0.9) g: (1.04-1.56) g: (10-15) mL, the heating reaction temperature is 80-90°C, the reaction time is 10-14 h, and the operation is repeated 2-4 times; in Q2, the dosage ratio of intermediate 1 and sulfuric acid solution is (0.5-0.9) g: (12-18) g, the volume fraction of sulfuric acid solution is 80vt%, the heating reaction temperature is 90-110°C, the reaction time is 9-11 h, and the pH is adjusted to 7-8.

[0017] Preferably, in Q3, the dosage ratio of intermediate 2, sulfuric acid solution, sodium nitrite and distilled water is (0.5-0.75) g: (20-30) g: (0.46-0.69) g: (1.38-2.12) mL, the volume fraction of sulfuric acid solution is 80vt%, the temperature is reduced to 8-10°C, the reaction time is continued for 1-2h, the temperature is increased to 90-100°C, the reaction time is 2-3h, and distilled water is added for extraction; in Q4, intermediate 3, toluene, chloride The dosage ratio of sulfoxide, additional toluene, p-chloroaniline and triethylamine is (0.5-0.7) g: (20-30) mL: (0.6-0.8) g: (30-45) mL: (0.4-0.6) g: (1-1.2) mL. The heating conditions are 100-110°C and the reaction time is 2-3h. The heating reaction temperature after adding p-chloroaniline is 80-85°C and the reaction time is 4-6h. The organic phase is washed with saturated sodium chloride and then with distilled water at 40-50°C.

[0018] Preferably, the method for preparing the composite flame retardant comprises the following steps:

[0019] S1: Add 3-glycidyloxypropyltrimethoxysilane, diphenylsilanediol and barium hydroxide into a container, stir and mix them evenly, introduce nitrogen, heat to react, and after the reaction is completed, vacuum dry to obtain a light yellow substance;

[0020] S2: Add a light yellow substance, boric acid and anhydrous ethanol into a container, stir, heat to condense and reflux for reaction, filter under reduced pressure to obtain a prepolymer, put the prepolymer into a vacuum oven to obtain a composite flame retardant.

[0021] In the above process, 3-glycidyloxypropyltrimethoxysilane and diphenylsilanediol are used as raw materials, anhydrous ethanol is used as solvent, and a light yellow substance is prepared by a non-hydrolytic sol-gel method. Subsequently, the light yellow substance and boric acid are dehydrated and condensed to prepare a composite flame retardant.

[0022] Preferably, in S1, the dosage ratio of 3-glycidyloxypropyltrimethoxysilane, diphenylsilanediol and barium hydroxide is (20-25) g: (27.46-35.12) g: (0.09-0.13) g, the heating reaction temperature is 80-85°C, the reaction time is 6-8h, the vacuum drying temperature is 60-70°C, and the drying time is 3-5h.

[0023] Preferably, in S2, the amount ratio of the light yellow substance, boric acid and anhydrous ethanol is (5-7.5) g: (1-1.5) g: (1-1.5) mL, the stirring time is 10-15 min, the heating condensation reflux reaction temperature is 170-180 ° C, the rotation speed is 500-700 rpm, the reaction time is 6-8 h, the temperature of the vacuum oven is 80-85 ° C, the vacuum degree is -2500~-3000 kPa, and the time is 20-24 h.

[0024] Preferably, the method for preparing the corrosion-resistant polypropylene edge banding material comprises the following steps:

[0025] Step 1: Add polypropylene, antioxidant, corrosion inhibitor, composite flame retardant, calcium carbonate and fuel into a mixing barrel, stir and mix evenly to obtain a mixture;

[0026] Step 2: Add the mixed material into a high-temperature melting machine for melting, extrusion, cooling, and solidification to obtain a corrosion-resistant polypropylene edge banding material.

[0027] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0028] 1. The present invention first uses 2,6-dichlorobenzonitrile, 1,2,4-triazole, sulfuric acid solution, sodium nitrite and p-chloroaniline as raw materials to prepare a corrosion inhibitor, and then uses 3-glycidyloxypropyltrimethoxysilane, diphenylsilanediol, barium hydroxide and boric acid as raw materials to prepare a composite flame retardant. The corrosion inhibitor and the composite flame retardant are simultaneously added to a polypropylene edge banding material, so that the obtained material has excellent corrosion resistance, heat resistance, flame retardancy and mechanical properties.

[0029] 2. The present invention adds the prepared corrosion-resistant agent to the polypropylene edge banding material, which can effectively improve the corrosion resistance and heat resistance of the material. The triazole group contained in the corrosion-resistant agent has excellent chemical stability, so that it can resist the erosion of various chemical media. The corrosion-resistant agent can also form hydrogen bonds and coordination bonds with the polypropylene material to form a close combination to form a dense protective film, which effectively blocks the corrosive medium; the benzene ring structure contained in it, as a stable aromatic structure, not only enhances the overall stability of the molecule, but also serves as a barrier to block the corrosive medium, and its high-temperature stability ensures that the material maintains stable performance at high temperatures; the amide bond contained in it, as a strong polar bond, enhances the intermolecular interaction force, makes the corrosion-resistant agent and polypropylene combine more closely, forms a firm protective film, and at the same time improves the heat resistance to prevent the breakage or recombination of chemical bonds at high temperatures.

[0030] 3. The present invention adds the prepared composite flame retardant to the polypropylene edge banding material, which can effectively improve the flame retardant properties and mechanical properties of the material. The silicon, boron and benzene rings contained in the composite flame retardant can form an effective flame retardant barrier to block heat transfer and flame spread. At the same time, the silicon-oxygen bonds and boron-oxygen bonds contained in the composite flame retardant can remain stable under high temperature conditions and slow down the combustion rate; the benzene ring structure absorbs heat to undergo thermal decomposition, generating gas and water vapor to dilute the combustible gas and reduce the combustion intensity; the silicon-oxygen bonds and cross-linking structures in the composite flame retardant enhance the interaction between polypropylene molecular chains and improve the mechanical properties. DETAILED DESCRIPTION

[0031] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Example 1: This example discloses a method for preparing a corrosion resistant agent, comprising the following steps:

[0033] Q1: Add 1.25 g of 2,6-dichlorobenzonitrile, 0.75 g of 1,2,4-triazole and 1.3 g of anhydrous potassium carbonate to a container containing 12.5 mL of N,N-dimethylformamide, heat at 90°C for 12 h, and filter under reduced pressure after the reaction. Repeat the operation 3 times to obtain intermediate 1;

[0034] Q2: 0.7 g of intermediate 1 was added to a container, and then 15 g of 80% by volume sulfuric acid solution was added, and the reaction was heated at 100°C for 10 hours. After the reaction was completed, distilled water was added, the pH was adjusted to 7, and the mixture was filtered under reduced pressure. The filtrate was extracted, dried and distilled under reduced pressure to obtain intermediate 2;

[0035] Q3: 0.63 g of intermediate 2 was added to a container placed in an ice bath, and 25 g of a sulfuric acid solution with a volume fraction of 80 vt% was added. After the temperature of the reaction liquid dropped to 8°C, 1.75 mL of distilled water containing 0.57 g of sodium nitrite was added dropwise. After the addition was completed, the reaction was continued for 1 hour, and then the temperature was raised to 100°C for reaction for 3 hours. After the reaction was completed, distilled water was added for extraction, dried, and distilled under reduced pressure to obtain intermediate 3;

[0036] Q4: Add 0.6g of intermediate 3 into a container with reflux and gas collection device containing 25mL of toluene. At 110℃, slowly add 0.7g of thionyl chloride and react for 3h. After negative pressure treatment, add 37.5mL of toluene, then add 0.5g of p-chloroaniline and heat at 85℃ for 6h. Add 1.1mL of triethylamine dropwise during the reaction. After the reaction, wash with saturated sodium chloride, let stand to separate, wash the organic phase with 40℃ distilled water, dry, filter, and evaporate to dryness under negative pressure to obtain a corrosion inhibitor.

[0037] This embodiment discloses a method for preparing a composite flame retardant, comprising the following steps:

[0038] S1: 22.5 g of 3-glycidyloxypropyltrimethoxysilane, 31.59 g of diphenylsilanediol and 0.11 g of barium hydroxide were added to a container, stirred and mixed evenly, nitrogen was introduced, and the mixture was heated at 85° C. for 8 h. After the reaction was completed, the mixture was vacuum dried at 65° C. for 4 h to obtain a light yellow substance;

[0039] S2: Add 6.25 g of light yellow substance, 1.25 g of boric acid and 1.25 mL of anhydrous ethanol into a container, stir for 15 min, heat to 180 ° C, condense and reflux at 700 rpm for 8 h, filter under reduced pressure to obtain a prepolymer, put the prepolymer into a vacuum oven at 85 ° C, -2500 kPa for 24 h to obtain a composite flame retardant.

[0040] The present embodiment discloses a corrosion-resistant polypropylene edge banding material, which is composed of the following components in parts by weight: 62.5 parts of polypropylene, 3.5 parts of antioxidant 1010, 4.5 parts of corrosion inhibitor, 3 parts of composite flame retardant, 11.5 parts of calcium carbonate, and 3 parts of dye.

[0041] This embodiment discloses a method for preparing a corrosion-resistant polypropylene edge banding material, comprising the following steps:

[0042] Step 1: Add polypropylene, antioxidant 1010, corrosion inhibitor, composite flame retardant, calcium carbonate and fuel into a mixing barrel, stir and mix evenly to obtain a mixture;

[0043] Step 2: Add the mixed material into a high-temperature melting machine for melting, extrusion, cooling, and solidification to obtain a corrosion-resistant polypropylene edge banding material.

[0044] Example 2: This example discloses a method for preparing a corrosion resistant agent, comprising the following steps:

[0045] Q1: Add 1.5 g 2,6-dichlorobenzonitrile, 0.6 g 1,2,4-triazole and 1.04 g anhydrous potassium carbonate into a container containing 10 mL N,N-dimethylformamide, heat at 90°C for 12 h, and filter under reduced pressure after the reaction. Repeat the operation 3 times to obtain intermediate 1;

[0046] Q2: 0.5 g of intermediate 1 was added to a container, and then 18 g of 80% by volume sulfuric acid solution was added, and the reaction was heated at 100°C for 10 hours. After the reaction was completed, distilled water was added, the pH was adjusted to 7, and the mixture was filtered under reduced pressure. The filtrate was extracted, dried and distilled under reduced pressure to obtain intermediate 2;

[0047] Q3: 0.5 g of intermediate 2 was added to a container placed in an ice bath, and 20 g of 80% sulfuric acid solution was added. After the temperature of the reaction solution dropped to 8°C, 1.38 mL of distilled water containing 0.46 g of sodium nitrite was added dropwise. After the addition was completed, the reaction was continued for 1 hour, and then the temperature was raised to 100°C for 3 hours. After the reaction was completed, distilled water was added for extraction, drying, and vacuum distillation was performed to obtain intermediate 3.

[0048] Q4: Add 0.5g of intermediate 3 into a container with reflux and gas collection device containing 30mL of toluene. At 110℃, slowly add 0.6g of thionyl chloride and react for 3h. After negative pressure treatment, add 30mL of toluene, then add 0.4g of p-chloroaniline and heat at 85℃ for 6h. During the reaction, add 1.2mL of triethylamine dropwise. After the reaction, wash with saturated sodium chloride, let stand to separate, wash the organic phase with 40℃ distilled water, dry, filter, and evaporate to dryness under negative pressure to obtain a corrosion inhibitor.

[0049] This embodiment discloses a method for preparing a composite flame retardant, comprising the following steps:

[0050] S1: 20 g of 3-glycidyloxypropyltrimethoxysilane, 27.46 g of diphenylsilanediol and 0.09 g of barium hydroxide were added to a container, stirred and mixed evenly, nitrogen was introduced, and the mixture was heated at 85° C. for 8 h. After the reaction was completed, the mixture was dried under vacuum at 65° C. for 4 h to obtain a light yellow substance;

[0051] S2: Add 5 g of light yellow substance, 1.5 g of boric acid and 1 mL of anhydrous ethanol into a container, stir for 15 min, heat to 180 ° C, condense and reflux at 700 rpm for 8 h, filter under reduced pressure to obtain a prepolymer, put the prepolymer into a vacuum oven at 85 ° C, -2500 kPa for 24 h to obtain a composite flame retardant.

[0052] The present embodiment discloses a corrosion-resistant polypropylene edge banding material, which is composed of the following components in parts by weight: 50 parts of polypropylene, 5 parts of antioxidant 1010, 3 parts of corrosion resistance agent, 2 parts of composite flame retardant, 8 parts of calcium carbonate, and 2 parts of dye.

[0053] This embodiment discloses a method for preparing a corrosion-resistant polypropylene edge banding material, comprising the following steps:

[0054] Step 1: Add polypropylene, antioxidant 1010, corrosion inhibitor, composite flame retardant, calcium carbonate and fuel into a mixing barrel, stir and mix evenly to obtain a mixture;

[0055] Step 2: Add the mixed material into a high-temperature melting machine for melting, extrusion, cooling, and solidification to obtain a corrosion-resistant polypropylene edge banding material.

[0056] Embodiment 3: This embodiment discloses a method for preparing a corrosion resistant agent, comprising the following steps:

[0057] Q1: Add 1 g of 2,6-dichlorobenzonitrile, 0.9 g of 1,2,4-triazole and 1.56 g of anhydrous potassium carbonate to a container containing 15 mL of N,N-dimethylformamide, heat at 90°C for 12 h, and filter under reduced pressure after the reaction. Repeat the operation 3 times to obtain intermediate 1;

[0058] Q2: 0.9 g of intermediate 1 was added to a container, and then 12 g of 80% by volume sulfuric acid solution was added, and the reaction was heated at 100°C for 10 hours. After the reaction was completed, distilled water was added, the pH was adjusted to 7, and the mixture was filtered under reduced pressure. The filtrate was extracted, dried and distilled under reduced pressure to obtain intermediate 2;

[0059] Q3: 0.75 g of intermediate 2 was added to a container placed in an ice bath, and 30 g of 80% sulfuric acid solution was added. After the temperature of the reaction solution dropped to 8°C, 2.12 mL of distilled water containing 0.69 g of sodium nitrite was added dropwise. After the addition was completed, the reaction was continued for 1 hour, and then the temperature was raised to 100°C for 3 hours. After the reaction was completed, distilled water was added for extraction, dried, and distilled under reduced pressure to obtain intermediate 3;

[0060] Q4: Add 0.7g of intermediate 3 into a container with reflux and gas collection device containing 20mL of toluene. At 110℃, slowly add 0.8g of thionyl chloride and react for 3h. After negative pressure treatment, add 45mL of toluene, then add 0.6g of p-chloroaniline and heat at 85℃ for 6h. During the reaction, add 1mL of triethylamine dropwise. After the reaction, wash with saturated sodium chloride, let stand to separate, wash the organic phase with 40℃ distilled water, dry, filter, and evaporate to dryness under negative pressure to obtain a corrosion inhibitor.

[0061] This embodiment discloses a method for preparing a composite flame retardant, comprising the following steps:

[0062] S1: 25 g of 3-glycidyloxypropyltrimethoxysilane, 35.12 g of diphenylsilanediol and 0.13 g of barium hydroxide were added to a container, stirred and mixed evenly, nitrogen was introduced, and the mixture was heated at 85° C. for 8 h. After the reaction was completed, the mixture was dried under vacuum at 65° C. for 4 h to obtain a light yellow substance;

[0063] S2: Add 7.5 g of light yellow substance, 1 g of boric acid and 1.5 mL of anhydrous ethanol into a container, stir for 15 min, heat to 180 ° C, condense and reflux at 700 rpm for 8 h, filter under reduced pressure to obtain a prepolymer, put the prepolymer into a vacuum oven at 85 ° C, -2500 kPa for 24 h to obtain a composite flame retardant.

[0064] The present embodiment discloses a corrosion-resistant polypropylene edge banding material, which is composed of the following components in parts by weight: 75 parts of polypropylene, 2 parts of antioxidant 1010, 6 parts of corrosion resistance agent, 4 parts of composite flame retardant, 15 parts of calcium carbonate, and 4 parts of dye.

[0065] This embodiment discloses a method for preparing a corrosion-resistant polypropylene edge banding material, comprising the following steps:

[0066] Step 1: Add polypropylene, antioxidant 1010, corrosion inhibitor, composite flame retardant, calcium carbonate and fuel into a mixing barrel, stir and mix evenly to obtain a mixture;

[0067] Step 2: Add the mixed material into a high-temperature melting machine for melting, extrusion, cooling, and solidification to obtain a corrosion-resistant polypropylene edge banding material.

[0068] Example 4: This example discloses a method for preparing a corrosion resistant agent, comprising the following steps:

[0069] Q1: Add 1.1 g 2,6-dichlorobenzonitrile, 0.7 g 1,2,4-triazole and 1.14 g anhydrous potassium carbonate to a container containing 11 mL N,N-dimethylformamide, heat at 90°C for 12 h, and filter under reduced pressure after the reaction. Repeat the operation 3 times to obtain intermediate 1;

[0070] Q2: 0.6 g of intermediate 1 was added to a container, and then 13 g of 80% by volume sulfuric acid solution was added, and the reaction was heated at 100°C for 10 hours. After the reaction was completed, distilled water was added, the pH was adjusted to 7, and the mixture was filtered under reduced pressure. The filtrate was extracted, dried and distilled under reduced pressure to obtain intermediate 2;

[0071] Q3: 0.55 g of intermediate 2 was added to a container placed in an ice bath, and 22 g of a sulfuric acid solution with a volume fraction of 80 vt% was added. After the temperature of the reaction liquid dropped to 8°C, 1.67 mL of distilled water containing 0.51 g of sodium nitrite was added dropwise. After the addition was completed, the reaction was continued for 1 hour, and then the temperature was raised to 100°C for reaction for 3 hours. After the reaction was completed, distilled water was added for extraction, dried, and distilled under reduced pressure to obtain intermediate 3;

[0072] Q4: Add 0.55g of intermediate 3 into a container with reflux and gas collection device containing 22mL of toluene. At 110℃, slowly add 0.65g of thionyl chloride and react for 3h. After negative pressure treatment, add 35mL of toluene, then add 0.45g of p-chloroaniline, heat at 85℃ and react for 6h. During the reaction, add 1.05mL of triethylamine dropwise. After the reaction, wash with saturated sodium chloride, let stand to separate, wash the organic phase with 40℃ distilled water, dry, filter, and evaporate to dryness under negative pressure to obtain a corrosion inhibitor.

[0073] This embodiment discloses a method for preparing a composite flame retardant, comprising the following steps:

[0074] S1: 22 g of 3-glycidyloxypropyltrimethoxysilane, 29.27 g of diphenylsilanediol and 0.1 g of barium hydroxide were added to a container, stirred and mixed evenly, nitrogen was introduced, and the mixture was heated at 85° C. for 8 h. After the reaction was completed, the mixture was vacuum dried at 65° C. for 4 h to obtain a light yellow substance;

[0075] S2: Add 5.5 g of light yellow substance, 1.1 g of boric acid and 1.1 mL of anhydrous ethanol into a container, stir for 15 min, heat to 180 ° C, condense and reflux at 700 rpm for 8 h, filter under reduced pressure to obtain a prepolymer, put the prepolymer into a vacuum oven at 85 ° C, -2500 kPa for 24 h to obtain a composite flame retardant.

[0076] The present embodiment discloses a corrosion-resistant polypropylene edge banding material, which is composed of the following components in parts by weight: 55 parts of polypropylene, 3 parts of antioxidant 1010, 4 parts of corrosion resistance agent, 2.5 parts of composite flame retardant, 10 parts of calcium carbonate, and 2.5 parts of dye.

[0077] This embodiment discloses a method for preparing a corrosion-resistant polypropylene edge banding material, comprising the following steps:

[0078] Step 1: Add polypropylene, antioxidant 1010, corrosion inhibitor, composite flame retardant, calcium carbonate and fuel into a mixing barrel, stir and mix evenly to obtain a mixture;

[0079] Step 2: Add the mixed material into a high-temperature melting machine for melting, extrusion, cooling, and solidification to obtain a corrosion-resistant polypropylene edge banding material.

[0080] Example 5: This example discloses a method for preparing a corrosion resistant agent, comprising the following steps:

[0081] Q1: Add 1.4 g 2,6-dichlorobenzonitrile, 0.8 g 1,2,4-triazole and 1.47 g anhydrous potassium carbonate into a container containing 14 mL N,N-dimethylformamide, heat at 90°C for 12 h, and filter under reduced pressure after the reaction. Repeat the operation 3 times to obtain intermediate 1;

[0082] Q2: 0.8 g of intermediate 1 was added to a container, and then 17 g of 80% by volume sulfuric acid solution was added, and the reaction was heated at 100°C for 10 hours. After the reaction was completed, distilled water was added, the pH was adjusted to 7, and the mixture was filtered under reduced pressure. The filtrate was extracted, dried and distilled under reduced pressure to obtain intermediate 2;

[0083] Q3: 0.72 g of intermediate 2 was added to a container placed in an ice bath, and 28 g of 80% by volume sulfuric acid solution was added. After the temperature of the reaction solution dropped to 8°C, 2.03 mL of distilled water containing 0.63 g of sodium nitrite was added dropwise. After the addition was completed, the reaction was continued for 1 hour, and then the temperature was raised to 100°C for reaction for 3 hours. After the reaction was completed, distilled water was added for extraction, dried, and distilled under reduced pressure to obtain intermediate 3;

[0084] Q4: Add 0.65g of intermediate 3 into a container with reflux and gas collection device containing 27mL of toluene. At 110℃, slowly add 0.75g of thionyl chloride and react for 3h. After negative pressure treatment, add 40mL of toluene, then add 0.55g of p-chloroaniline, heat at 85℃ and react for 6h. During the reaction, add 1.15mL of triethylamine dropwise. After the reaction, wash with saturated sodium chloride, let stand to separate, wash the organic phase with 40℃ distilled water, dry, filter, and evaporate to dryness under negative pressure to obtain a corrosion inhibitor.

[0085] This embodiment discloses a method for preparing a composite flame retardant, comprising the following steps:

[0086] S1: 23 g of 3-glycidyloxypropyltrimethoxysilane, 34.08 g of diphenylsilanediol and 0.12 g of barium hydroxide were added to a container, stirred and mixed evenly, nitrogen was introduced, and the mixture was heated at 85° C. for 8 h. After the reaction was completed, the mixture was vacuum dried at 65° C. for 4 h to obtain a light yellow substance;

[0087] S2: Add 6.5 g of light yellow substance, 1.4 g of boric acid and 1.4 mL of anhydrous ethanol into a container, stir for 15 min, heat to 180 ° C, condense and reflux at 700 rpm for 8 h, filter under reduced pressure to obtain a prepolymer, put the prepolymer into a vacuum oven at 85 ° C, -2500 kPa for 24 h to obtain a composite flame retardant.

[0088] The present embodiment discloses a corrosion-resistant polypropylene edge banding material, which is composed of the following components in parts by weight: 70 parts of polypropylene, 4 parts of antioxidant 1010, 5 parts of corrosion resistance agent, 3.5 parts of composite flame retardant, 14 parts of calcium carbonate, and 3.5 parts of dye.

[0089] This embodiment discloses a method for preparing a corrosion-resistant polypropylene edge banding material, comprising the following steps:

[0090] Step 1: Add polypropylene, antioxidant 1010, corrosion inhibitor, composite flame retardant, calcium carbonate and fuel into a mixing barrel, stir and mix evenly to obtain a mixture;

[0091] Step 2: Add the mixed material into a high-temperature melting machine for melting, extrusion, cooling, and solidification to obtain a corrosion-resistant polypropylene edge banding material.

[0092] Comparative Example 1: Compared with Example 1, in the process of preparing the corrosion-resistant agent in Comparative Example 1, 2,6-dichlorobenzonitrile is not added, and other conditions remain unchanged.

[0093] Comparative Example 2: Compared with Example 1, in Comparative Example 2, during the preparation of the composite flame retardant, 3-glycidyloxypropyltrimethoxysilane was not added, and other conditions remained unchanged.

[0094] Comparative Example 3: Compared with Example 1, in Comparative Example 3, during the process of preparing the corrosion-resistant polypropylene edge banding material, no corrosion-resistant agent is added, and other conditions remain unchanged.

[0095] Comparative Example 4: Compared with Example 1, in Comparative Example 4, during the process of preparing the corrosion-resistant polypropylene edge banding material, no composite flame retardant is added, and other conditions remain unchanged.

[0096] Experimental Example: The polypropylene edge banding materials prepared in Examples 1-5 and Comparative Examples 1-4 were subjected to performance tests. The prepared samples were placed in 40wt% sodium hydroxide solution and 50vt% hydrochloric acid solution, respectively, and placed in a constant temperature and humidity chamber for 90 days. The mass of the samples before and after the experiment was weighed, and the weight change percentage before and after was calculated. The heat resistance of the samples was tested according to ISO-75-2-2013, and the flame retardant performance of the samples was tested according to GB / T 2406.2-2009. The test results are shown in Table 1:

[0097] Table 1

[0098] It can be seen from the test results in Table 1 that the polypropylene edge banding materials prepared in Examples 1-5 of the present invention have excellent corrosion resistance, heat resistance and flame retardancy. By comparing Comparative Example 1 with Examples 1-5, it can be seen that the addition of 2,6-dichlorobenzonitrile can effectively improve the corrosion resistance and heat resistance of the polypropylene edge banding material; by comparing Comparative Example 2 with Examples 1-5, it can be seen that the addition of 3-glycidyloxypropyltrimethoxysilane can effectively improve the flame retardancy of the polypropylene edge banding material; by comparing Comparative Example 3 with Examples 1-5, it can be seen that the addition of a corrosion inhibitor can effectively improve the corrosion resistance and heat resistance of the polypropylene edge banding material; by comparing Comparative Example 4 with Examples 1-5, it can be seen that the addition of a composite flame retardant can effectively improve the flame retardancy of the polypropylene edge banding material.

[0099] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

[0100] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A corrosion-resistant polypropylene edge banding material, characterized in that: The invention is composed of the following components in parts by weight: 50-75 parts of polypropylene, 2-5 parts of antioxidant, 3-6 parts of corrosion inhibitor, 2-4 parts of composite flame retardant, 8-15 parts of calcium carbonate and 2-4 parts of dye. The corrosion inhibitor is prepared from 2,6-dichlorobenzonitrile, 1,2,4-triazole, sulfuric acid solution, sodium nitrite and p-chloroaniline, and the composite flame retardant is prepared from 3-glycidyloxypropyltrimethoxysilane, diphenylsilanediol, barium hydroxide and boric acid.

2. The corrosion-resistant polypropylene edge banding material according to claim 1, characterized in that: The antioxidant is composed of one or more of antioxidant 1010 , antioxidant 1076 , antioxidant 168 and antioxidant 626 .

3. The corrosion-resistant polypropylene edge banding material according to claim 1, characterized in that: The preparation method of the corrosion resistant agent comprises the following steps: Q1: Add 2,6-dichlorobenzonitrile, 1,2,4-triazole and anhydrous potassium carbonate to a container containing N,N-dimethylformamide, heat to react, and after the reaction is completed, filter under reduced pressure and repeat the operation to obtain intermediate 1; Q2: Add intermediate 1 to a container, then add sulfuric acid solution, heat to react, add distilled water after the reaction is completed, adjust the pH, filter under reduced pressure, extract, dry and distill the filtrate under reduced pressure to obtain intermediate 2; Q3: Add intermediate 2 to a container placed in an ice bath, add sulfuric acid solution, wait for the temperature of the reaction solution to drop, dropwise add distilled water containing sodium nitrite, continue the reaction after the dropwise addition is complete, then increase the temperature to react, extract, dry, and distill under reduced pressure after the reaction is complete to obtain intermediate 3; Q4: Add intermediate 3 to a container with toluene and a reflux and gas collection device, slowly add thionyl chloride under heating conditions to react, treat under negative pressure, add toluene, add p-chloroaniline, heat to react, add triethylamine dropwise during the reaction, wash after the reaction, let stand to separate, wash the organic phase, dry, filter, evaporate to dryness under negative pressure to obtain a corrosion inhibitor.

4. The corrosion-resistant polypropylene edge banding material according to claim 3, characterized in that: In Q1, the dosage ratio of 2,6-dichlorobenzonitrile, 1,2,4-triazole, anhydrous potassium carbonate and N,N-dimethylformamide is (1-1.5) g: (0.6-0.9) g: (1.04-1.56) g: (10-15) mL, the heating reaction temperature is 80-90° C., the reaction time is 10-14 h, and the operation is repeated 2-4 times; in Q2, the dosage ratio of intermediate 1 and sulfuric acid solution is (0.5-0.9) g: (12-18) g, the volume fraction of sulfuric acid solution is 80vt%, the heating reaction temperature is 90-110° C., the reaction time is 9-11 h, and the pH is adjusted to 7-8.

5. The corrosion-resistant polypropylene edge banding material according to claim 3, characterized in that: In the Q3, the dosage ratio of intermediate 2, sulfuric acid solution, sodium nitrite and distilled water is (0.5-0.75) g: (20-30) g: (0.46-0.69) g: (1.38-2.12) mL, the volume fraction of sulfuric acid solution is 80vt%, the temperature is reduced to 8-10°C, the reaction time is continued for 1-2h, the temperature is increased to 90-100°C, the reaction time is 2-3h, and distilled water is added for extraction; in the Q4, intermediate 3, toluene, thionyl chloride, The amount ratio of added toluene, p-chloroaniline and triethylamine is (0.5-0.7) g: (20-30) mL: (0.6-0.8) g: (30-45) mL: (0.4-0.6) g: (1-1.2) mL, the heating condition temperature is 100-110°C, the reaction time is 2-3h, the heating reaction temperature after adding p-chloroaniline is 80-85°C, the reaction time is 4-6h, the organic phase is washed with saturated sodium chloride, and then washed with distilled water at 40-50°C.

6. The corrosion-resistant polypropylene edge banding material according to claim 1, characterized in that: The preparation method of the composite flame retardant comprises the following steps: S1: Add 3-glycidyloxypropyltrimethoxysilane, diphenylsilanediol and barium hydroxide into a container, stir and mix them evenly, introduce nitrogen, heat to react, and after the reaction is completed, vacuum dry to obtain a light yellow substance; S2: Add a light yellow substance, boric acid and anhydrous ethanol into a container, stir, heat to condense and reflux for reaction, filter under reduced pressure to obtain a prepolymer, put the prepolymer into a vacuum oven to obtain a composite flame retardant.

7. The corrosion-resistant polypropylene edge banding material according to claim 6, characterized in that: In the S1, the dosage ratio of 3-glycidyloxypropyltrimethoxysilane, diphenylsilanediol and barium hydroxide is (20-25) g: (27.46-35.12) g: (0.09-0.13) g, the heating reaction temperature is 80-85° C., the reaction time is 6-8 h, the vacuum drying temperature is 60-70° C., and the drying time is 3-5 h.

8. The corrosion-resistant polypropylene edge banding material according to claim 6, characterized in that: In the S2, the amount ratio of the light yellow substance, boric acid and anhydrous ethanol is (5-7.5) g: (1-1.5) g: (1-1.5) mL, the stirring time is 10-15 min, the heating condensation reflux reaction temperature is 170-180° C., the rotation speed is 500-700 rpm, the reaction time is 6-8 h, the temperature of the vacuum oven is 80-85° C., the vacuum degree is -2500~-3000 kPa, and the reaction time is 20-24 h.

9. A method for preparing a corrosion-resistant polypropylene edge banding material according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step 1: Add polypropylene, antioxidant, corrosion inhibitor, composite flame retardant, calcium carbonate and fuel into a mixing barrel, stir and mix evenly to obtain a mixture; Step 2: Add the mixed material into a high-temperature melting machine for melting, extrusion, cooling, and solidification to obtain a corrosion-resistant polypropylene edge banding material.

Citation Information

Patent Citations

  • A high-rigidity, high-heat-sealing-strength polypropylene material and its preparation method

    CN112574500B

  • Corrosion-resistant polyarylester composite material and preparation method thereof

    CN113308096A

  • Organic silicon-boron flame retardant as well as preparation method and application thereof

    CN115974908A

  • High-flame-retardant polypropylene composite material and preparation method thereof

    CN118931034A

  • Silicon-boron flame retardant for PE (polyethylene) matrix, preparation method of silicon-boron flame retardant and PE-based composite material

    CN119285961A

Cited By

  • Preparation method of high-performance ceramic take-off and landing platform of unmanned aerial vehicle

    CN120081655A

  • High-ring stiffness power tube and preparation method thereof

    CN120158011A

  • Weather-resistant polyamide composition and preparation method thereof

    CN120647929A